CLINICAL CASE OF ACUTE MYOCARDIAL INFARCTION IN PATIENTS WITH MICROVASCULAR ANGINA - Yu. I. Minyuk; E. V. Saliyeva; Z. S. Tamoyan; Ju. R. Urmanova; L. U. Taipova; A. Kh. Khasanov (Евразийский Кардиологический Журнал)
Purpose. To describe a clinical case of coronary burden without stenosing lesions of the main branches of the coronary arteries in a patient with microvascular angina with subsequent development of myocardial infarction with the formation of ischemic hypokinesis of the anterior-apical region of the left ventricle in the absence of elevated levels of serum markers of myocardial necrosis.Materials and methods. The study is based on a single clinical case. The object of the study is the patient in whom there were complaints of pressing pain localized behind the sternum and radiating to the left arm, accompanied by a mixed shortness of breath that occurred at rest, poorly stoped short-range nitrates and narcotic analgesics, sharp General weakness. Under primary inspection state of ailing average extent of gravity, consciousness clear, position active, skin integuments and visible mucous of clean, conventional painting. The patient was evaluated laboratory parameters, ECG, echo-cardiography (ECHO-kg), chest x-ray (OGK), coronary angiography (CAG), followed by transfer to the emergency Department of cardiology.Results. The conducted clinical and laboratory study revealed the presence of leukocytosis in the patient with the clinic of acute coronary syndrome, without increasing cardiospecific enzymes (CFC, CFC-MB, troponin test), as well as high activity of coagulogram indicators (fibrinogen, ACTV, rfmc). When conducting radiography of OGK in direct projection-congestive lungs, a picture of chronic bronchitis in combination with left ventricular myocardial hypertrophy.Conclusion. In the presented clinical case was described an example of development of microvascular lesions in coronary arteries in a patient with manifestation of acute coronary syndrome with severe prolonged chest pain and repolarization changes on ECG and without elevated levels of serum markers of myocardial necrosis, which probably leads to the definition of this state as fragile (or sharp) microvascular dysfunction with myocardial infarction.